CHASE: A Large-Scale and Pragmatic Chinese Dataset for Cross-Database Context-Dependent Text-to-SQL - GUO, Jiaqi; Si, Ziliang; WANG, Yu; LIU, Qian; FAN, Ming; Lou, Jian-Guang; YANG, Zijiang; LIU, Ting (ACL-IJCNLP 2021, 2021)
The cross-database context-dependent Text-to-SQL (XDTS) problem has attracted considerable attention in recent years due to its wide range of potential applications. However, we identify two biases in existing datasets for XDTS: (1) a high proportion of context independent questions and (2) a high proportion of easy SQL queries. These biases conceal the major challenges in XDTS to some extent. In this work, we present CHASE, a large-scale and pragmatic Chinese dataset for XDTS. It consists of 5,459 coherent question sequences (17,940 questions with their SQL queries annotated) over 280 databases, in which only 35% of questions are context independent, and 28% of SQL queries are easy. We experiment on CHASE with three state-of-the-art XDTS approaches. The best approach only achieves an exact match accuracy of 40% over all questions and 16% over all question sequences, indicating that CHASE highlights the challenging problems of XDTS. We believe that CHASE can provide fertile soil for addressing the problems.